Investigation of Hyperglycaemia and Associated Factors among Pregnant Women Attending Antenatal at Mulago Hospital, Directorate of Obstetrics and Gynaecology, Kawempe. - Muhoozi, Derek Matsiko (Student's Journal of Health Research Africa, 2020)
Background: This study aimed at establishing the prevalence and factors associated with hyperglycemia in pregnancy among women attending treatment at antenatal care at the Directorate of obstetrics and gynaecology at Kawempe under the following objectives; to determine the prevalence of hyperglycemia in pregnancy, to establish the factors associated with hyperglycemia in pregnancy. Methods: The study was cross-sectional and experimental in design that recruited 333 participants from age 18 years and above. The consented participants filled a questionnaire that was taking history and demographics. A blood sample was taken for blood glucose testing and a urine sample was also collected. Data was entered in Epidata 3.1 and exported to SPSS 17.0 for analysis. Descriptive statistics and multivariate analysis was used to determine prevalence and factors associated with hyperglycemia in pregnancy Results: Laboratory tests revealed that the prevalence of hyperglycemia was 25.3% (84). The following factors were significantly associated with hyperglycemia in pregnancy; age37 years and above (p-value 0.013* OR 2.34), and high Body Mass Index (BMI) (p-value 0.002* OR 3.744). Gravidity of 3-4 times (p-value 0.003*OR3.782), >=5 times (p-value <0.001*and OR3.099), parity of >=5 children (p-value 0.003*OR 3.642), first degree hyperglycaemia (P-value <0.031*OR 5.152), high blood pressure during this pregnancy (0.012*OR 3.622) and high blood pressure while not pregnant (p-value 0.012*OR 1.274). Conclusion and recommendations: Gestational hyperglycemia is common among women attending care at the directorate of Obstetrics and Gynecology at Kawempe. the commonest factors associated with hyperglycemia in pregnancy are high Body mass index, history of hypertension, history of hyperglycemia, high parity high gravidity, there is no relationship between hyperglycemia and sexually transmitted diseases like HIV, and syphilis.